A conceptual framework for teaching computational thinking in personalized OERs - Jewoong Moon; Jaewoo Do; Daeyeoul Lee; Gi Woong Choi (Smart Learning Environments, 2020)
Abstract Interests towards teaching programming skills have risen recently in the realm of computing education. Learning how to program not only enables learners to develop computing applications, but it can also enhance learners’ computational thinking (CT) practice. CT refers to learners’ ability to approach ill-structured tasks systematically based on algorithmic thinking in computing. Along with growing academic interests towards CT in recent studies, researchers have emphasized the role of teaching programming in facilitating learners’ problem-solving skills. Emerging OERs have expanded learners’ opportunities to engage in hands-on programming exercises; yet a challenge still remains as to how learners’ programming exercises can be tailored to accommodate individual differences in terms of learners’ digital literacy skills. There is still a lack of in-depth discussions on how to support learners’ personalized learning experiences during programming exercises associated with CT. This study hence proposes a conceptual framework that seeks to consider how to promotelearners’ personalized learning experiences and enhance their CT skills in OERs. Through extensive reviewing of literature, this study provides several implications for further research.